2022
DOI: 10.3390/ma15144954
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Strain Transmitted through Prostheses on Implants with Two Different Macro-Structures and Connection during Insertion and Loading Phase: An In Vitro Study

Abstract: Background: The purpose of this study was to measure and compare the strain levels in the peri-implant bone as generated by the blade-like implant (BLI) and the screw-type implant (STI) with two different internal connections (hexagonal and conical) and with a 1:1 and 2:1 crown/implant (C/I) ratio. Methods: The implants (BLI and STI) were placed into sawbones according to the manufacturer’s protocol. Two strain gauges, horizontal and vertical to the implant axis, were placed around each implant on the bone sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The stress caused by the mastication loads on a dental implant creates dynamic strains on the surrounding tissues, thus affecting the rehabilitation process [ 6 , 14 , 31 ]. In view of this, the surface particles and roughness guarantee a differential load transfer depending on their physical and chemical characteristics [ 6 , 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stress caused by the mastication loads on a dental implant creates dynamic strains on the surrounding tissues, thus affecting the rehabilitation process [ 6 , 14 , 31 ]. In view of this, the surface particles and roughness guarantee a differential load transfer depending on their physical and chemical characteristics [ 6 , 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stress caused by the mastication loads on a dental implant creates dynamic strains on the surrounding tissues, thus affecting the rehabilitation process [ 6 , 14 , 31 ]. In view of this, the surface particles and roughness guarantee a differential load transfer depending on their physical and chemical characteristics [ 6 , 14 , 31 ]. Therefore, the presence of a configuration with the highest roughness and reduced number of particles on the HA-blasted and bland acid etching implants may have a considerably better impact on the adhesion and load transfer during rehabilitation [ 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarchitecture of a biomaterial, including the number of particles and their size, distribution, and density, dramatically affects its interaction with tissues and cells and influences the mechanical properties of the scaffold itself [27]. In particular, it has been observed that the texture of the implant surface significantly affects cells both in vitro and in vivo, encouraging osseointegration [7][8][9]27] and likely extending its duration and long-term stability [8,11]. To establish whether or not particles were evenly distributed throughout the surface and would have an impact on cell adhesion and proliferation, we thus analyzed the surface mean particle area, distance, spacing, and number (Figure 2A-J, Table 1).…”
Section: Implants' Morphological Characterizationmentioning
confidence: 99%
“…Indeed, the macro-and micro-topography of oral implants dramatically affect their stability and duration [7][8][9]. Specifically, the charge, geometry, and chemical composition of the surface, in particular, ensure optimal load transfer to the bone and the surrounding tissues, attract differentiated or undifferentiated progenitor cells from the native tissue, and induce regeneration and differentiation of host progenitor cells favoring, in fact, osseointegration and long-term stability of the implant [8,11].…”
Section: Introductionmentioning
confidence: 99%